অনুরণন: Revival of Anderkilla Shahi Jame Mosque - Eva, Ramisa Yeameen Chowdhury (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2019.